The Concept of Public Works in India - Ratnesh, Pandey (International Journal of Engineering and Management Sciences, 2018)
The objective of this paper is to understand the concept of public work in India. Nowadays we may approach a wide and broad understanding of public work on international level. One aspect is working for the government. Another one is associated with fighting unemployment and providing work possibility for the unemployed (by doing this decreasing poverty). It may also be understood as participated in governmental financed construction programmes and NREG is one such programme which helps to generate employment for the poor people in India. In this paper various aspects about public works in India are discussed.